(untitled) (Scientific journal of the Fergana State University, 2023)
This article analyzes the history of the «Institute of physiotherapy» in 1923-1950, its activities, achievements and problems in providing the medical services to the population, the problems of personnel. Furthermore, the activity of the Institute of physiotherapy in 1923-1950, created in 1923.